Eastern Philosophy And Environmental Ethics: The Contribution Of Harmony Concepts To Sustainable Development - Judijanto, Loso; Ndlovu, Sibusiso Ndlovu; Taylor, Liam (Journal of Humanities Research Sustainability, 2025)
Background. The global search for effective environmental ethics beyond dominant anthropocentric models has increased interest in alternative worldviews. Eastern philosophies, with their emphasis on balance and interconnectedness, offer a profound source of ecological wisdom for fostering a more sustainable human-nature relationship. Purpose. This study analyzes the core concept of ‘harmony’ within Taoism, Buddhism, and Confucianism and articulates its contribution to the contemporary framework of sustainable development. Method. The research employs a qualitative, philosophical-hermeneutic methodology, conducting a textual analysis of classical sources to distill ethical principles related to environmental harmony. Results. The findings reveal that foundational concepts like the Tao (natural flow), Paticcasamupp?da (interconnectedness), and Tian-Ren He Yi (unity of Heaven and Humanity) promote a non-anthropocentric, holistic ethic. This perspective values moderation and nature’s intrinsic worth, directly supporting the integrated goals of sustainable development. Conclusion. Eastern concepts of harmony provide a robust ethical foundation for sustainability. They foster an ethic of relational responsibility and long-term balance, offering a crucial alternative to purely utilitarian or rights-based environmental frameworks.